2012
DOI: 10.1051/0004-6361/201118621
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Cepheids in the Large Magellanic Cloud

Abstract: Context. The properties of variable stars can give independent constraints on the star formation history of the host galaxy, by determining the age and metallicity of the parent population. Aims. We investigate the pulsation properties of 84 Anomalous Cepheids (ACs) detected by the OGLE-III survey in the Large Magellanic Cloud (LMC), in order to understand the formation mechanism and the characteristics of the parent population they came from. Methods. We used an updated theoretical pulsation scenario to deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 61 publications
5
37
0
Order By: Relevance
“…ACs fill a space on the PL-diagram above the RRL and T2Cs by ∼0.5 to ∼2 magnitudes (as the period increases), but do not reach into the CC region. Caputo et al (2004) investigated the possibility that they do continue to the PL relation of CCs, but Fiorentino & Monelli (2012) concluded that they are metal-poor stars that would not evolve into the CC IS region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACs fill a space on the PL-diagram above the RRL and T2Cs by ∼0.5 to ∼2 magnitudes (as the period increases), but do not reach into the CC region. Caputo et al (2004) investigated the possibility that they do continue to the PL relation of CCs, but Fiorentino & Monelli (2012) concluded that they are metal-poor stars that would not evolve into the CC IS region.…”
Section: Introductionmentioning
confidence: 99%
“…Quoting the results of Vassiliadis & Wood (1993), Wallerstein (2002) gives the initial mass of the brighter T2Cs (the RVT) to be around 1 M ⊙ . In the case of ACs pulsation models have been considered by various authors to find masses in the range 1.3-2.2 M ⊙ (for Z = 0.0001 and 0.0004, Bono et al (1997b), Marconi et al (2004)), or, specifically 1.2 ± 0.2 M ⊙ for the ACs in the LMC (Fiorentino & Monelli 2012). Recently, Martínez-Vázquez et al (2016) find ∼ 1.5 M ⊙ for four ACs in the Sculptor dSph galaxy.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical investigations into the origins of Anomalous Cepheids indicate these stars are either (1) evolved, intermediate-age (< 5 Gyr) stars, or (2) the evolved products of mass transfer in old (> 10 Gyr) binary systems, but with no definitive means to distinguish either mechanism (Bono et al 1997). Nevertheless, the observational evidence better supports the interpretation that Anomalous Cepheids are metal-poor, intermediate age variables: (1) the spatial distribution of Anomalous Cepheids in the LMC shows they are not coincident with the older stellar populations (Fiorentino & Monelli 2012), (2) (blue), M31 data for And01, And03, And02 and And06 (green) and data for Leo T (red) Gallart et al 2004). In comparison to theoretical predictions, the scatter is attributed to the mass of each individual star.…”
Section: Age Distributions In M31 Satellites From Anomalous Cepheidsmentioning
confidence: 95%
“…Even in well-studied systems like the Large Magellanic Cloud (LMC), such tracers have proven invaluable for proper reconstruction of the SFH (Fiorentino & Monelli 2012). At M31 distances, the Cepheid-type variables are particularly useful due to their intrinsic luminosity -several magnitudes brighter than the horizontal branch (HB) -and can be efficiently photometered from the ground -unlike RR Lyrae which require HST temporal monitoring at M31 distance (Sandage & Tammann 2006;Mateo et al 1995).…”
Section: Age Distributions In M31 Satellites From Anomalous Cepheidsmentioning
confidence: 99%
See 1 more Smart Citation